Xunzi: Moral education and transformation. Issue 4 (1st October 2020) - Lu, Xiufen
ABSTRACT: A fair amount of recent Xunzi scholarship has focused on the problem of moral transformation. The problem being addressed supposedly arises this way. According to Xunzi, human nature is innately or inherently evil; individuals, nevertheless, can become moral agents capable to embracing and loving moral principles. Unfortunately, Xunzi does not provide any account of how individuals whose characters are inherently evil can transformed into full moral agents. Several scholars have proposed various ways in which Xunzi could address the problems, but all are unsatisfactory for various reasons. In this paper, I will develop my own reading of Xunzi's moral philosophy. My approach is to put Xunzi in the context of classical Confucianism, a tradition that shaped Xunzi's thinking on his metaphysical assumption about the world, his reverence for the wisdom of sage kings, and his emphasis on education as the necessary condition for virtue development.